Evaluasi Kebijakan Pengelolaan Sampah di TPA Air Dingin Berdasarkan Analisis SWOT dan Peraturan Lingkungan - Rama Nanda; Aldri Frinaldi; Rembrandt Rembrandt; Dasman Lanin (Jurnal Sains dan Ilmu Terapan, 2024)
Effective and sustainable waste management is a major challenge in meeting increasingly stringent environmental regulations. This study aims to evaluate the waste management policy at the TPA Air Dingin using a weighted SWOT analysis, considering the factors of strengths, weaknesses, opportunities, and threats. Based on the weighting results, the strength (2.05) and opportunity (2.05) factors indicate significant potential for improving waste management, particularly through supportive regulations and technological advancements. Meanwhile, weaknesses (1.05) and threats (1.35), including low community participation and increasing waste volume, represent challenges that need to be addressed. Strategic recommendations include leveraging waste management technology, enhancing recycling facilities, and conducting awareness campaigns to increase public participation. The findings of this study are expected to provide strategic directions for improving waste management policies at TPA Air Dingin in accordance with applicable environmental regulations.